Pelatihan Pengemasan Produk Keripik Pisang Dan Stik Kulit Pisang Kepada Kelompok Tani Desa Lomaer, Sampang - Andre Yusuf Trisna Putra; Nove Kartika Erliyanti (STIKes Ibnu Sina Ajibarang, 2024)
Lomaer Village is one of the villages in Bangkalan Regency which has superior banana products. Bananas are processed into banana chips and banana peel sticks. However, the products that have been produced have not been packaged and labeled properly. Therefore, packaging training was carried out on banana chips and banana peel sticks for the Lomaer Village Farmers Group. Activities are carried out in two stages, namely, preparation and training. The training was held on Sunday, September, 12th 2021. The training participants were 30 members of the Lomaer Farmers Group, starting at 08.00-14.00 at the Lomaer Village Hall. Packaging training begins with a presentation of material about the function, purpose and appropriate packaging methods for food products. Next, the practice of packaging banana chips and banana peel sticks was carried out, then continued with labeling the packaging. The results of this training were able to increase participants' knowledge about the purpose, types and benefits of packaging and were able to practice packaging for banana chips and banana peel sticks